Action research: a strategy in community education - Ismail, Maimunah; Abdul Wahat, Nor Wahiza (The Journal of Global Business Management, 2008)
This paper briefly discusses the essence of action research in terms of meaning and significance in community education. Based on its emphases that are participatory, educational, collaborative and contextual bound, action research has been identified as one of the strategies in generating knowledge that could be used to help community undergo sustainable social improvements. This paper describes how action research, being problem-based, action-based, responsive, and practical can serve as one of the best research approaches in dealing with community issues. The discussion on its cyclic framework consisting of situational analysis, intervention and evaluation is also pursued in this paper as to give a clear picture on the interlinked process involved in the conduct of such research. Readers will be able to understand that action research actually means research and action that can be simultaneously achieved by the researcher and all participants involved in the study. Towards the end of the discussion, several points are shared on several factors contributing to the success of community learning through action research, such as worth of the program, enjoyment, freedom, and sense of belonging. Some highlights from real community cases in Malaysia were showcased to indicate the practicality and applicability of action research.